Active fractions of methanol crude obtained from acacia seyal gum and their anti-proliferative effects against human breast cancer cell lines - Elnour, Ahmed Adam Hassan M.; Mirghani, Mohamed Elwathig Saeed; Kabbashi, Nassereldeen Ahmed; Daddiouaissa, Djabir; Musa, Khalid Hamid; Alam, Md Zahangir; Nour, Abdurahman Hamid (Global Journals In., 2020)
Background: This study is on Acacia seyal gum, which is an exudate from Talha (Acacia seyal) tree. It provides a rich source of prebiotic that is used traditionally in folk medicine. Aims: The anti-proliferative effect (APE) of Acacia seyal gum (ASG) and Prebio-T-commercial (PTC) samples on human breast cancer (MCF-7) cell lines and their antioxidant activities (AA) were investigated. Methods: The methanol crude extracts of both Acacia seyal gum and Prebio-T-commercial were fractioned into acetone and methanol, respectively. The antiproliferative effect on human breast cancer cell lines for each fraction was examined using sulphorhodamine assay (SRB assay). Methanol crude extracts and their active compositions were analysed carefully using gas chromatography-mass spectrometry technique. Results: The most anti-proliferative effect was detected in the sample collected from Prebio-T-commercial (IC50=8.97µg/mL) as compared to Acacia seyal gum (IC50=9.56µg/mL). Regarding total phenolic content (TPC), the methanol crude extracts values are 694±2.58mg, GAE/100g for Prebio-T-commercial as compared to 155.78±2.58, GAE/100g for Acacia seyal gum. However, both acetone and methanol fractions of Acacia seyal gum and Prebio-T-commercial were found to be highly anti-proliferative to human breast cancer. For bioactive compounds determinations, the methanol crude extract from Acacia seyal gum is mainly dominated by Isovitamin C (42.37%), Crypton (5.86%), and Hydroquinone (4.86%) as major components. Conclusion: Finally, the antioxidant and anti-proliferative properties of the active fraction have shown some evidence regarding its use in traditional medicine as well as the prevention of cancer cell growth. This suggests the potential use of their bioactive compounds as natural anticancer agents.